Pengembangan Media Pembelajaran IPA Berbasis Android Dalam Meningkatan Kwalitas Pembelajaran Siswa SMA - Nurhadi; Muhammad Sobri (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
The method of learning becomes one of the factors that is very influential, especially for students' academic achievement. Nowadays students are required to be more active in expanding the knowledge they not only get from teaching and learning activities in school, but they can also add knowledge such as from a learning application that they can learn by themselves to hone their understanding of subjects. In the subject of Natural Science (IPA), often the methods or methods used by teachers in teaching are still many that are difficult to understand by the students, the existing learning media less interest of students to study harder, and students sometimes consider easy subjects IPA. Learning Media in High School (SMA) visually displayed in the form of applications that can be accessed with Android-based phones is expected to improve the quality of learning, especially in science subjects.